2003
DOI: 10.1016/s0378-1097(03)00691-8
|View full text |Cite
|
Sign up to set email alerts
|

PCR and RAPD identification ofL. plantarumstrains isolated from ovine milk and cheese. Geographical distribution of strains

Abstract: Lactobacilli, and specifically Lactobacillus plantarum, are an important group of microorganisms in ovine cheeses, even though they are not ordinarily included in the starter cultures added. The present study effected counts of lactobacilli in Roncal Protected Designation of Origin (PDO) milk and cheese samples and isolated a total of 1026 strains. The strains were identified to species level by polymerase chain reaction (PCR) using L. plantarum-specific oligonucleotide primers, and the strains belonging to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 27 publications
2
12
0
2
Order By: Relevance
“…However, ANOVA did not reveal any significant relationship between the percentage of the two subspecies and the origin of the milk samples. This finding agrees with the observations published by Oneca et al (2003) on wild Lactobacillus plantarum populations of raw milks produced in the Roncal PDO area but disagrees with those of Corroler et al (1998) who reported that 80% of isolates from the Bocage Falaisien area in Normandy were members of subsp. lactis genotype, while 70% of the Bessin isolates were members of subsp.…”
Section: Genotypic Diversity Of Strains Of L Lactissupporting
confidence: 77%
“…However, ANOVA did not reveal any significant relationship between the percentage of the two subspecies and the origin of the milk samples. This finding agrees with the observations published by Oneca et al (2003) on wild Lactobacillus plantarum populations of raw milks produced in the Roncal PDO area but disagrees with those of Corroler et al (1998) who reported that 80% of isolates from the Bocage Falaisien area in Normandy were members of subsp. lactis genotype, while 70% of the Bessin isolates were members of subsp.…”
Section: Genotypic Diversity Of Strains Of L Lactissupporting
confidence: 77%
“…The specific environmental conditions prevailing in a fermenting food substrate promote the growth of some of these bacteria. Lactobacillus plantarum is predominantly found in fermented food and feed products, and is implicated in the processing of food for human consumption, such as sauerkraut, dry fermented sausage, wine and green olive fermentations and cheese making (Ruiz-Barba et al, 1994;Oneca et al, 2003), as well as in animal nutrition, such as crop preservation (Merry et al, 1995), fish and crab waste fermentation (Abazinge et al, 1993) and poultry by-product fermentation (Urlings et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Genotypic methods used for L. plantarum strain typing are typically PCR-based methods, for example randomly amplified polymorphic DNA (Johansson et al, 1995;Oneca et al, 2003;Elegado et al, 2004) or variations of restriction enzyme analysis, for example ribotyping (Yansanjav et al, 2003;Rodas et al, 2005) and pulsed-field gel electrophoresis (Sánchez et al, 2004). Multilocus sequence typing (MLST) has recently been shown to be a powerful technique for bacterial typing.…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacillus plantarum is a common inhabitant of the human gastrointestinal tract (3), but it is also encountered in a variety of environmental niches, such as dairy, meat, and vegetable fermentations (25,39). L. plantarum is widely used in industrial and traditional production of fermented plant, food, and feed products, such as sauerkraut, sausage, cabbage, olives, and silage (14,31,41).…”
mentioning
confidence: 99%